2009
DOI: 10.1590/s0066-782x2009000600009
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento de uma coorte de pacientes com infarto agudo do miocárdio com supradesnivelamento do segmento ST

Abstract: Patients were suitable for reperfusion, but one third of them did not have the procedure. Two deaths during evolution. The most predominant treatment was CTA, with low morbidity. Low global lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
(5 reference statements)
0
5
2
Order By: Relevance
“…Studies on acute coronary syndrome report that most AMI patients had three or more risk factors and the most prevalent were: hypertension, dyslipidemia and family history, and physical inactivity showed no relevance [3,4]. In this study, physical inactivity was reported by 82.79% of patients and smoking by 36.54%, showing no significance when related to the studied variables.…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Studies on acute coronary syndrome report that most AMI patients had three or more risk factors and the most prevalent were: hypertension, dyslipidemia and family history, and physical inactivity showed no relevance [3,4]. In this study, physical inactivity was reported by 82.79% of patients and smoking by 36.54%, showing no significance when related to the studied variables.…”
Section: Discussioncontrasting
confidence: 66%
“…A study performed in Rio de Janeiro, involving patients diagnosed with AMI with ST segment elevation (SST) showed that 67.7% reached the emergency room after three hours of the onset of the first symptom and 8.4% after 12 hours [ 3]. Another study performed in Rio Grande do Sul showed that 88% of patients with SST sought emergency care within an hour, and the average was 3h59min to 2h55min.…”
Section: * Monitoring During Transport Of the Patient To The Unitmentioning
confidence: 99%
See 3 more Smart Citations